Antibody-drug conjugates: what drives their progress? - Pander, Giulia; Uhl, Philipp; Kühl, Nikos; Haberkorn, Uwe; Anderl, Jan; Mier, Walter (Drug discovery today, 2022)
Antibody-drug conjugates (ADCs) are on the brink of widespread use for the targeted treatment of cancer. ADCs manage the toxicity of drugs with unacceptable narrow therapeutic windows by guiding highly toxic compounds to the target cells, thereby sparing healthy cells. In this review, we describe approved ADCs and discuss their modes of action, together with medicinal chemical aspects, to evaluate the potential for improvement and to combat tumor-acquired resistance. A recent research focus has centered on the stimulation of immune responses to induce immunogenic cell death and the influence on the tumor microenvironment to enhance bystander effects.